Deep Learning Implementation Strategies in Indonesia National Curriculum: A Culturally Responsive Framework for Pinrang Regency - Pada, Damir; S, Jumadi (International Journal Education and Computer Studies (IJECS), 2025)
This research develops implementation strategies for Deep Learning approaches within Indonesia's National Curriculum specifically adapted for Pinrang Regency's educational settings. The study employs descriptive qualitative methodology through document analysis and literature review to create strategic frameworks addressing regional educational challenges while honoring Buginese cultural heritage. Five primary strategic domains emerged: conceptual foundation development integrating "sipakainge" and "sipakatau" values; national curriculum adaptation through low-tech high-impact approaches; practical school-level implementation utilizing local phenomena and collaborative "assitulung-tulungeng" patterns; educator capacity building via district-based learning communities; and evaluation systems with situational indicators for sustainability. The research demonstrates that Deep Learning principles can be successfully adapted to diverse local conditions while maintaining pedagogical rigor through systematic integration of cultural wisdom, economic potential, and available resources. The strategic framework creates authentic learning experiences engaging students meaningfully while building 21st-century skills through community partnerships, intergenerational learning, and cultural documentation projects. Findings reveal that effective educational reform requires adaptive strategies responding to local conditions rather than standardized approaches, emphasizing pedagogical creativity over technological sophistication. The framework provides practical guidance for educational leaders implementing culturally responsive Deep Learning approaches, offering replication potential across Indonesian regions through systematic balancing of national standards with local distinctiveness. Success measurement encompasses not only academic outcomes but also cultural identity strengthening, community cohesion enhancement, and students' sense of place development within local and global communities.